The immediate effects of self-myofacial release on flexibility, jump performance and dynamic balance ability - Zhang, Q.; Trama, R.; Fouré, A.; Hautier, C. A. (Journal of Human Kinetics, 2020)
Self-myofascial release (SMR) is a popular method to potentially increase the compliance and extensibility of the fascia and reduce muscle stiffness. The purpose of this study was to examine the acute effects of posterior muscle chain SMR on flexibility, vertical jump performance and balance ability. Eighteen young participants volunteered to take part in this crossover design study. They performed two self-massage sessions in randomized order separated by at least one week. One session consisted of posterior muscle chain SMR whereas the other one was performed on the upper limbs as a control intervention (CON). Flexibility was measured with the Toe Touch Test (TTT), Weight-Bearing Lunge Test (WBLT), and Straight Leg Raise Test (SLR). Jump performance was evaluated during a squat jump, a counter movement jump and a stiffness jump. Dynamic balance ability was assessed through the Star Excursion Balance Test. All these variables were measured before and after each intervention. A significant increase in flexibility (+3.5 ± 1.8 cm, +1.6 ± 1.0°, and +7.7 ± 4.0° for the TTT, WLBT, and SLR, respectively, p < 0.003) and balance performance (4.8 ± 3.9 cm, p < 0.003) was observed following SMR intervention compared to CON. Conversely, jumping performance was unchanged in both groups. SMR improves joint flexibility and dynamic balance ability.